Substoichiometry and tantalum dependent thermal stability of α-structured W-Ta-B thin films. (October 2018) - Moraes, V.; Fuger, C.; Paneta, V.; Primetzhofer, D.; Polcik, P.; Bolvardi, H.; Arndt, M.; Riedl, H.; Mayrhofer, P.H.
Abstract: Physical vapor deposited (PVD) WB2 thin films crystallize in the α-AlB2 -prototype structure rather than in their thermodynamically stable ω-W2 B5-z -prototype structure. Contrary to the majority of α-AlB2 -type transition metal diborides (TMB2 ), α-WB2 exhibits a more ductile character. Combining density functional theory and sophisticated experiments, we show that the stability of α-WB2 thin films is basically influenced by point defects such as vacancies present in PVD materials. With the help of α-TaB2 (one of the most ductile TMB2 with high preference for α-AlB2 -type), the thermally driven decomposition and phase transformation of α-W1-x Tax B2-z to the ω-W2 B5-z -type can be shifted to temperatures above 1200 °C. Graphical abstract: Unlabelled Image